(untitled) (World Bulletin of Management and Law, 2025)
In the conditions of unstable financial markets, effective risk management is the key to successful investments. This article is devoted to the use of Big Data and machine learning technologies to create a predictive model capable of assessing and reducing financial risks. An algorithm for combining data from various sources is described and the results of testing the model on real investment examples are demonstrated.